Association Between Hemostatic Profile and Migraine: A Mendelian Randomization Analysis. (18th May 2021) - Guo, Yanjun; Rist, Pamela M.; Sabater-Lleal, Maria; de Vries, Paul; Smith, Nicholas; Ridker, Paul M; Kurth, Tobias; Chasman, Daniel I.
Abstract : Objective: To assess support for a causal relationship between hemostatic measures and migraine susceptibility using genetic instrumental analysis. Methods: Two-sample Mendelian randomization instrumental analyses leveraging available genome-wide association study (GWAS) summary statistics were applied to hemostatic measures as potentially causal for migraine and its subtypes, migraine with aura (MA) and migraine without aura (MO). Twelve blood-based measures of hemostasis were examined, including plasma level or activity of 8 hemostatic factors and 2 fibrinopeptides together with 2 hemostasis clinical tests. Results: There were significant instrumental effects between increased coagulation factor VIII activity (FVIII; odds ratio [95% confidence interval] 1.05 [1.03, 1.08]/SD, p = 6.08 × 10 −05 ), von Willebrand factor level (vWF; 1.05 [1.03, 1.08]/SD, p = 2.25 × 10 −06 ), and phosphorylated fibrinopeptide A level (1.13 [1.07, 1.19]/SD, p = 5.44 × 10 −06 ) with migraine susceptibility. When extended to migraine subtypes, FVIII, vWF, and phosphorylated fibrinopeptide A showed slightly stronger effects with MA than overall migraine. Fibrinogen level was inversely linked with MA (0.76 [0.64, 0.91]/SD, p = 2.32 × 10 −03 ) but not overall migraine. None of the hemostatic factors was linked with MO. In sensitivity analysis, effects for fibrinogen and phosphorylated fibrinopeptide A were robust, whereas independent effects of FVIII and vWF could not be distinguished, and FVIII associations were potentially affected by pleiotropy at the ABO locus. Causal effects from migraine to the hemostatic measures were not supported in reverse Mendelian randomization. However, MA was not included due to lack of instruments. Conclusions: The findings support potential causality of increased FVIII, vWF, and phosphorylated fibrinopeptide A and decreased fibrinogen in migraine susceptibility, especially for MA, potentially revealing etiologic relationships between hemostasis and migraine.